1994
DOI: 10.1007/bf00196848
|View full text |Cite
|
Sign up to set email alerts
|

Shoot neoformation in clones of Fraxinus pennsylvanica in relation to genotype, site and pruning treatments

Abstract: Summary. Four clones of Fraxinus pennsylvanica var. subintegerrima (Vahl) Fern. were planted in replicated trials at two sites in Manitoba (Morden and Winnipeg) to investigate shoot growth and leaf neoformation in relation to genotype, environment and pruning treatment over a 3 year period. Significant differences were found among clones, years and sites for shoot length and numbers of neoformed leaves. Neoformation was highest shortly after transplanting and then declined. An increase in neoformation was evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 26 publications
3
19
0
Order By: Relevance
“…In addition, the trees were less exposed to freezing injury at this site and were clearly more vigorous (Davidson and Remphrey 1993). Remphrey (1989) concluded that environmental influences were important in bud development in mature F. pennsylvanica based on year to year variation.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, the trees were less exposed to freezing injury at this site and were clearly more vigorous (Davidson and Remphrey 1993). Remphrey (1989) concluded that environmental influences were important in bud development in mature F. pennsylvanica based on year to year variation.…”
Section: Discussionmentioning
confidence: 98%
“…Gill (1971) reported one of the first studies on white ash, although it was limited to comparing only 15 terminal buds of opposite branches. More detailed work by Remphrey and Davidson (1994) and Davidson and Remphrey (1994) has shown that green ash has the capacity for both preformation and neoformation; the latter is where shoots are not entirely preformed in the resting bud and a proportion of the leaves is formed during the growth season. This was the first report of neoformation in Fraxinus and was shown to be an important part of the plant's recovery strategy after pruning or the loss of terminal buds in late spring frosts.…”
Section: Shoot Growthmentioning
confidence: 98%
“…This likely led to greater structural complexity, and may have increased intrashoot competition (Hackett, 1985), resulting in the general decline in neoformed growth as time from pruning elapsed. Davidson and Remphrey (1994) found a similar decline in neoformed growth as Fraxinus pennsylvanica trees matured, and their architectural complexity increased.…”
Section: Discussionmentioning
confidence: 70%
“…Davidson and Remphrey (1994) found that pruning, as well as the removal of buds, and thus potentially competing shoots, increased neoformation in Fraxinus pennsylvanica Marsh. However, their study was limited to young trees (4 -5 years-old).…”
mentioning
confidence: 98%